Eucharistic Theology as a Condition of Eucharistic Revival According to John Paul II and Benedict XVI - Migut, Bogusław (Verbum Vitae, 2025)
The answer to the question of whether the Eucharistic theology of John Paul II and Benedict XVI in its selected aspects can constitute the foundation for the Eucharistic renewal of the Church is absolutely affirmative. This is proven by the depth of their theology, which consists in linking the Eucharist to the most important theological issues. An analysis of the teachings of John Paul II and Benedict XVI confirms the thesis put forward in the introduction to this paper that the Eucharist is one of the most important theological topics. The renewal and revival of Eucharistic life cannot consist only of pastoral activity, but in the constant discovery of the theological depth of this sacrament and the delight of its richness. Only such a deeply theological vision of the Eucharist can protect it from being made shallow and marginalized. John Paul II presents the Eucharist as: (1 ) the place where God humbles Himself to such an extent that His Majesty is hidden, and the reason for this is love; (2) the place of Christ’s loving us “to the end,” where He unites Himself to us, where the spousal nature of Christ’s body transforms our bodies into His image; and (3) the place of revelation of God to man and of man to man. Benedict XVI presents the Eucharist as: (1) the principle and place of action of the Divine Logos, who was the principle and model of the creation of the world and of man, who took on flesh and became man and began anew the original relationship of creation with its Creator through obedience, and who now continues to transform the world through the Eucharist, transforming the human heart into His own image; (2) the place of action of the Logos and the worship of God by us joined to the Logos and in the image of the Logos; (3) the place of transforming our eros love (love of desire, passion, a climbing) for God and neighbor into agape love, that is, making the gift of self.